Reviewing from a Distance: Uncovering Asymmetric Moderations of Spatial and Temporal Distances Between Sentiment Negativity and Rating - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (MIS Quarterly)

Toss a Coin to your Host - How Guests End up Paying for the Cost of Regulatory Policies - Müller, Michelle; Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Proceedings of the 41th International Conference on Information Systems (ICIS))

Goal Achievement, Subsequent User Effort and the Moderating Role of Goal Difficulty - Gutt, Dominik; von Rechenberg, Tobias; Kundisch, Dennis (Journal of Business Research)

Design of Review Systems – A Strategic Instrument to shape Online Reviewing Behavior and Economic Outcomes - Gutt, Dominik; Neumann, Jürgen; Zimmermann, Steffen; Kundisch, Dennis; Chen, J. (Journal of Strategic Information Systems)

Money Makes the Reviewer Go Round – Ambivalent Effects of Online Review Elicitation in B2B Markets - Neumann, Jürgen; Gutt, Dominik (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

When does Local Status Matter? – The Relationship between Reviewer Location and Perceived Usefulness of Online Reviews - Neumann, Jürgen; Gutt, Dominik; Görzen, Thomas; Kundisch, Dennis (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

The Virtues of Anonymity - An Empirical Investigation of the Relationship between B2B Online Ratings and Reviewer Self-Disclosure - Gutt, Dominik; Neumann, Jürgen (Proceedings of the 27th European Conference on Information Systems (ECIS))

He Who Pays the Piper Calls the Tune: Online Review Elicitation by Sellers and Third-Party Platforms in B2B Markets - Neumann, Jürgen; Gutt, Dominik (Proceedings of the 27th European Conference on Information Systems (ECIS))

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Competition and Online Rating Distributions - Gutt, Dominik; Herrmann, Philipp; Rahman, Mohammad (Information Systems Research)

Heart over Heels? An Empirical Analysis of the Relationship between Emotions and Review Helpfulness for Experience and Credence Goods - Müller, Michelle; Gutt, Dominik (Wirtschaftsinformatik Proceedings 2019)

Essays on Drivers and Economic Outcomes of Online-Reviews - Gutt, Dominik

The App Updating Conundrum: Implications of Platform’s Rating Resetting on Developers’ Behavior - Gutt, Dominik; Neumann, Jürgen; Jabr, W.; Kundisch, Dennis (Proceedings of the 40th International Conference on Information Systems (ICIS))

In the Eye of the Beholder? – Empirically Decomposing Different Economic Implications of the Online Rating Variance - Gutt, Dominik (Proceedings of the 25th European Conference on Information Systems (ECIS))

The Traveling Reviewer Problem - Exploring the Relationship Between Offline Locations and Online Rating Behavior - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Conference Abstracts of the Symposium on Statistical Challenges in Electronic Commerce Research (SCECR))

The Traveling Reviewer Problem - Exploring the Relationship Between Offline Locations and Online Rating Behavior - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Workshop on IS Design and Economic Behavior (ISDEB))

When Local Praise Becomes Cheap Talk - Analyzing the Relationship between Reviewer Location and Usefulness of Online Reviews - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis; van Straaten, Dirk (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
With a growing number of online reviews, it becomes increasingly important for customers and online review platforms to find groups of reviewers who write useful reviews. Customers who review local offline businesses such as restaurants can identify themselves as locals or travelers and thus implicitly assign themselves to a specific reviewer group. This study investigates the relationship between identifying as a local and the perceived usefulness of their online reviews. Using data from Yelp.com, we empirically test hypotheses derived from attribution theory. Our results suggest that neutral and negative reviews by locals tend to be perceived as more useful than reviews by travelers. Positive reviews by locals, however, are not perceived as more useful. These findings provide significant practical implications for online review platforms and local offline businesses.

Sorting Out the Lemons - Identifying Product Failures in Online Reviews and their Relationship with Sales - Gutt, Dominik (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
It is well-established that both average online ratings and the number of ratings positively impact product sales. Yet, the economic implications of the information contained in the online review texts is not that well understood. In this study, we contribute to the understanding of online review texts and its economic implications by conducting and validating an unsupervised machine learning algorithm, the latent dirichlet allocation, to identify online reviews that mention product failures. Furthermore, we show that the textual information on product failures are associated with lower product sales. Our results help online review system designers, e.g., amazon, to identify these reviews and to make them easily accessible to potential customers to support the customer’s purchasing decision. Academics can build on our results by applying our validated topic identification strategy and by linking reviews mentioning product failure to a range of different outcomes.

Beschreib mir deine Wohnung und ich sag dir wer du bist - Eine explorative Analyse von Gastgeberpersönlichkeiten auf Airbnb - Müller, Michelle; Gutt, Dominik; Neumann, Jürgen (Multikonferenz Wirtschaftsinformatik (MKWI) 2018)

You can’t buy my rating! On the pivotal effect of an unconditional gift on rating behavior - Gutt, Dominik; Schlangenotto, Darius; Kundisch, Dennis (Wirtschaftsinformatik Proceedings, St. Gallen, Switzerland)
The importance of online ratings on sales is widely acknowledged. Firms need to find ways of increasing the number of ratings and rating scores, but how they can achieve this effectively is less well established. In this paper we analyze the impact of an unconditional gift on customers’ rating behavior in an online field experiment. Contrary to prevalent advice, our results suggest that providing a gift is not necessarily beneficial. Younger customers are significantly less likely to rate when exposed to an unconditional gift. Regression analysis reveals that age serves as a moderator and older customers even respond slightly positive to a gift. Having detected a negative effect of gifts on rating behavior provides first indicative evidence of a possible crowding out of intrinsic motivation in the context of online ratings. This has direct implications for practitioners considering the usage of gifts to elicit online ratings.

Was bedeutet die Transformation der Märkte im digitalen Zeitalter? Ökonomische Grundlagen - Kundisch, Dennis; Gutt, Dominik (Digitale Ökonomie - Wie verändern sich die Märkte?)